تصورات الطلاب حول مهنة المحاسبة وعمل المحاسب دليل من كلية الاقتصاد في جامعة تشرين - عيسى ريم (Latakia University Journal - Economic and Legal Sciences Series, 2017)
خلقت التغيرات في بيئة الأعمال حاجة ملحة إلى المزيد من الأفراد المبدعين في مهنة المحاسبة. تهدف هذه الدراسة إلى تقديم أدلة من كلية الاقتصاد، جامعة تشرين حول تصورات الطلاب عن مهنة المحاسبة وعمل المحاسب، وتحديد العوامل التي تؤثر في هذه التصورات، والتعرف على تصورات الطلاب حول تقييم المجتمع لمهنة المحاسبة بالمقارنة مع تسعة مهن أخرى. بينت الدراسة أن الطلاب يملكون نظرة تقليدية لمهنة المحاسبة باعتبارها مملة، ثابتة، مدفوعة بالامتثال، دقيقة، وفردية التوجه. اعتبر الطلاب أن الأساتذة، والمقررات الدراسية أهم العوامل التي تؤثر في تصوراتهم حول مهنة المحاسبة وعمل المحاسب. هم يعتقدون أن المجتمع يقيم مهنة المحاسبة بتقدير جيد، ولكن بدرجة أقل من معظم المهن الأخرى. تشير النتائج إلى أنه إذا أرادت الهيئات المهنية للمحاسبة أن تكون ناجحة في جذب الطلاب إلى مهنة المحاسبة، يجب أن تسعى إلى التعاون مع المؤسسات التعليمية للتأثير على تصورات الطلاب. Changes in the business environment have created a perceived need for more creative individuals in the accounting profession. The study aimed to present evidence about the students’ perceptions of accountancy profession and accountant work from the faculty of Economics at Tishreen university, identify the factors that influence these perceptions, and find out the students’ perceptions of the status of accounting profession according to the society’s view. The study found that students hold a traditional view of accounting profession considering it boring, fixed, compliance driven, precise, and solitary. The students considered university lecturers and subjects as the main factors that influence their perception of accounting profession and the work of accountant. They believe that society evaluates the accounting profession as being a good one, but to a lesser degree than most other professions The results indicate that if the professional accounting bodies want to be successful in attracting students to accounting profession, it must seek to corporate with educational institutions to influence students’ perceptions .